2015
DOI: 10.18034/abr.v5i2.58
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Financial Performance of Property Andreal Estate Companies Listed at Indonesia Stock Exchange

Abstract: Financial performance is one of the factors used by investors in buying shares. For companies, improving financial performance is a must in order to keep the company's stock attractive to investors. Financial statements published by the company are a reflection of the company's financial performance. These financial statements are the result of the accounting process that is intended to provide the financial information of a company. The financial information can be used by users for making investment decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…Financial performance is usually measured through return on assets [2][3][4][5] and return on equity [6][7][8]. Financial performance has been stated in the literature as being affected by certain factors such as liquidity, ownership, age and size [9]. Also, other factors may affect financial performance, such as leverage, productivity, solvency and assets turnover, and these may change in the face of a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Financial performance is usually measured through return on assets [2][3][4][5] and return on equity [6][7][8]. Financial performance has been stated in the literature as being affected by certain factors such as liquidity, ownership, age and size [9]. Also, other factors may affect financial performance, such as leverage, productivity, solvency and assets turnover, and these may change in the face of a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Edi trading in Malaysia. Deitiana and Habibuw (2015) have shown that there is no effect between the liquidity ratio and financial profitability of companies. Although the fast ratio tests the short-term liquidity status of a firm and measures the capacity of a company to fulfill its short-term commitments for the most liquid assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This demonstrates the degree to which the borrowed money is being used by a company (Pandey, 2007). Many previous studies used the leverage ratio to calculate capital structure determinants (Chen et al, 2017;Deitiana & Habibuw, 2015;Mandiefe, 2016;Singh & Sharma, 2016). Bose et al (2017) indicated that leverage ratio was reported as a percentage of total debt separated by total assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They agreed with the assertion made by the theory of comparative market power that large size firms were generally competent and were able to leverage their market power by using their products to generate the highest revenues. Conversely, Deitiana and Habibuw (2015) in their analysis on the size of selected organizations discovered that size was not considered to be a key element of organizational efficiency. However, Zadeh and Eskandari (2012) did argue that firm size did have a different quality and quantity for different countries.…”
Section: Literature Reviewmentioning
confidence: 99%